The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1111/j.1432-1033.1997.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Selective P‐nitrophenyl‐ester‐hydrolyzing Antibodies Elicited by a P‐nitrobenzyl Phosphonate Hapten

Abstract: A number of monoclonal antibodies elicited against a nitrobenzyl (Nbzl)-phosphonate transition-state analogue (TSA), and which were selected for the hydrolysis of the corresponding Nbzl-ester, were also found to catalyze the hydrolysis of the analogous p-nitrophenyl(Np) ester with notable efficiency and specificity. The activity towards the Np-ester is higher in terms of rates (kca,; as expected from the higher intrinsic reactivity of Np-esters) ; however, the rate acceleration (k,,,/k,,,,,) is close to or lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The bottom of the pocket, where the p-nitrobenzyl moiety of the ligand is found, has a marked hydrophobic character: seven residues make apolar contacts with the p-nitrobenzyl group. The tight Van der Waals interactions between p-nitrobenzyl and the Fab account for the specificity of D2.3 for pararelative to ortho-nitrosubstituted ligands (10), because the corresponding change in the position of substitution would require a significant rearrangement of the Fab residues to be accommodated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bottom of the pocket, where the p-nitrobenzyl moiety of the ligand is found, has a marked hydrophobic character: seven residues make apolar contacts with the p-nitrobenzyl group. The tight Van der Waals interactions between p-nitrobenzyl and the Fab account for the specificity of D2.3 for pararelative to ortho-nitrosubstituted ligands (10), because the corresponding change in the position of substitution would require a significant rearrangement of the Fab residues to be accommodated.…”
Section: Resultsmentioning
confidence: 99%
“…1); it was obtained by immunizing BALB͞c mice with a protein conjugate of the phosphonate hapten 3 and identified by screening the entire repertoire of hybridomas for catalytic activity (9). D2.3 is the most efficient of the family of antibodies obtained and it accelerates the target reaction by a factor of 10 5 (10). We previously determined the x-ray structure of the Fab D2.3 complexed with TSA 3 at 1.9-Å resolution (8).…”
mentioning
confidence: 99%
“…In the catalyzed reactions, these residues would be expected to form hydrogen bonds to the oxyanion of the transition state produced by hydroxyl anion or the nucleophilic residue's attack on the substrates, lowering the activation energy. Antibodies D2.3, D2.4, D2.5, and 6D9 catalyze the hydrolytic reaction by transition-state stabilization. In addition to transition-state stabilization, other catalytic mechanisms, such as nucleophilic and/or general-base catalysis, have been observed or suggested for antibodies 43C9, 48G7, CNJ206, 17E8, 29G11, and 7C8. , Although the haptens employed to generate these antibodies do not have a structural entity that induces amino acid residues capable of contributing to nucleophilic and general-base catalysis, antibody diversity has the potential to provide catalytic antibodies possessing these properties in addition to the transition-state stabilization.…”
Section: Hydrolytic Antibodies Generated Against Transition-state Ana...mentioning
confidence: 99%
“…Antibodies D2.3, D2.4, and D2.4 generated with phosphonate 4 catalyzed the hydrolysis of 5 (Scheme , Table ). These antibodies had rate accelerations that correlated to their affinity for the transition-state analogue relative to the substrate ( K S / K TSA = k cat / k uncat ) (Table ) . The mechanism of the reactions catalyzed by these antibodies is delineated by the transition-state stabilization and by X-ray structural studies .…”
Section: 2 Comparison Of a Set Of Antibodies Generated Against A Sing...mentioning
confidence: 99%
“…Switching from p-nitrobenzyl to p-nitrophenyl esters served to overcome the reactivity problem and, as discussed above, also reduced product inhibition. § § Tawfik et al (17) subsequently reported p-nitrophenyl ester hydrolytic antibodies elicited by a p-nitrobenzyl phosphonate hapten. In this context, the results reported at about the same time by Jacobsen and Schultz are of interest (18).…”
Section: G3 Catalyzed Cyclizationsmentioning
confidence: 99%